Tai Chi for the prophylaxis of episodic migraine: protocol of a non-inferiority randomized controlled trial with mechanism exploration - Yao Jie Xie; Xiaoli Liao; Stanley Sai-chuen Hui; Longben Tian; Wing Fai Yeung; Alexander Yuk-lun Lau; Stefanos Tyrovolas; Yang Gao; Xiangyan Chen (BMC, 2023)
Abstract Background Migraine is a complex neurovascular disorder with considerable clinical, social and economic issues. Tai chi has the potential to be an alternative prophylactic treatment for migraine with high safety since the adverse effects and limited efficacy of available medications. Aims The proposed study aims to compare the prophylaxis efficacy of 24-week Tai Chi training on migraine attacks with the standard prophylactic medication; and to explore the mechanism of Tai Chi in preventing migraine attacks by analyzing the associations between changes of migraine attacks and changes of neurovascular functions and inflammatory makers. Method This is a two-arm parallel non-inferiority randomized controlled trial. In total 220 Hong Kong Chinese women aged 18-65 years with diagnosis of episodic migraine will be recruited and randomized to either the Tai Chi training group or the standard prophylactic medication group with 1:1 ratio, and receive the 24 weeks of modified 33-short form Yang-style Tai Chi training and the standard prophylactic medications, respectively. A 24-week follow-up will be implemented for both groups. For efficacy examination, the primary outcome was the frequency of migraine attacks measured by the migraine diary; and for the mechanism exploration, the primary outcome was the volume and number of white matter hyperintensity (WMH) measured by magnetic resonance imaging (MRI). The measurements will be conducted at the baseline, 24th weeks, and 48th weeks. Linear mixed model will be adopted to comprehensively analyze the changes of variables within and between groups. Discussion Given the importance of reducing disease burden and financial cost of migraine attacks, the findings of this study will provide new insights regarding the role of Tai Chi in alleviating migraine burden and further shed light on the mechanism action of Tai Chi on preventing headache attacks. Trial registration ClinicalTrials.gov NCT05690737. Registered on January 28, 2023.